Stream Mercury Export in Response to Contemporary Timber Harvesting Methods (Pacific Coastal Mountains, Oregon, USA) - Eckley, Chris S. (Environ Sci Technol, 2018)
Land-use activities can alter hydrological and biogeochemical processes that can affect the fate, transformation, and transport of mercury (Hg). Previous studies in boreal forests have shown that forestry operations can have profound but variable effects on Hg export and methylmercury (MeHg) formation. The Pacific Northwest is an important timber producing region that receives large atmospheric Hg loads, but the impact of forest harvesting on Hg mobilization has not been directly studied and was the focus of our investigation. Stream discharge was measured continuously, and Hg and MeHg concentrations were measured monthly for 1.5 years following logging in three paired harvested and unharvested (control) catchments. There was no significant difference in particulate-bound Hg concentrations or loads in the harvested and unharvested catchments which may have resulted from forestry practices aimed at minimizing erosion. However, the harvested catchments had significantly higher discharge (32%), filtered Hg concentrations (28%), filtered Hg loads (80%), and dissolved organic carbon (DOC) loads (40%) compared to forested catchments. MeHg concentrations were low (mostly <0.05 ng L(−1)) in harvested, unharvested, and downstream samples due to well-drained/unsaturated soil conditions and steep slopes with high energy eroding stream channels that were not conducive to the development of anoxic conditions that support methylation. These results have important implications for the role forestry operations have in affecting catchment retention and export of Hg pollution.